International Electron Devices Meeting 1999. Technical Digest (Cat. No.99CH36318)
DOI: 10.1109/iedm.1999.824268
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature (Ba,Sr)TiO/sub 3/ capacitor process integration (LTB) technology for gigabit scaled DRAMs

Abstract: Low femperature (600°C) (Ba, Sr)Ti03 (BST) capacitor process integration (LTB) based on SrRu03 (SRO) electrode is proposed to achieve gigabit scaled and embedded DRAMs. BST crystallizing temperature is successfully reduced by SRO, which has the same perovskite structure as BST film. Chemical Mechanical polishing (CMP) and O3 water etching are developed for a storage node (SN) electrode and a plate (PL) electrode patterning. A new low temperature post anneal method is also proposed in order to reduce oxygen vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The low-temperature ͑Ͻ500°C͒ metallorganic chemical vapor deposition ͑MOCVD͒ process has been extensively studied for producing STO and BSTO thin films for DRAM applications due to its good film step coverage over a severe 3D surface topology, and nondamaging deposition on the underlying electrode stack. 11,12 However, conformal deposition over the entire surface area of such an extreme geometry in terms of the chemical composition as well as the thickness has not necessarily been confirmed even for lowtemperature MOCVD processes. The authors have reported extensive experimental results on the composition and thickness variations of the MOCVD STO and BSTO films deposited at wafer temperatures ranging from 420 to 440°C on a capacitor hole pattern with dimensions of 0.15 ϫ 0.40 ϫ 0.57 ͑depth͒ m 3 where two shower-head-type and one dome-type MOCVD chamber with two different precursor sets were used.…”
mentioning
confidence: 99%
“…The low-temperature ͑Ͻ500°C͒ metallorganic chemical vapor deposition ͑MOCVD͒ process has been extensively studied for producing STO and BSTO thin films for DRAM applications due to its good film step coverage over a severe 3D surface topology, and nondamaging deposition on the underlying electrode stack. 11,12 However, conformal deposition over the entire surface area of such an extreme geometry in terms of the chemical composition as well as the thickness has not necessarily been confirmed even for lowtemperature MOCVD processes. The authors have reported extensive experimental results on the composition and thickness variations of the MOCVD STO and BSTO films deposited at wafer temperatures ranging from 420 to 440°C on a capacitor hole pattern with dimensions of 0.15 ϫ 0.40 ϫ 0.57 ͑depth͒ m 3 where two shower-head-type and one dome-type MOCVD chamber with two different precursor sets were used.…”
mentioning
confidence: 99%
“…The low temperature ͑Ͻ500°C͒ metallorganic ͑MO͒ chemical vapor deposition ͑CVD͒ process for producing ͑Ba,Sr͒TiO 3 ͑BST͒ thin films is becoming crucial for merged memory and logic ͑MML͒ and dynamic random access memory devices ͑DRAM͒ having minimum feature sizes less than 0.13 m. [1][2][3] Good film step coverage over a severe three-dimensional surface topography and nondamaging deposition on the underlying electrode stack are key merits of the low temperature process over the high temperature ͑Ͼ600°C͒ process. The expected capacitor structure for 0.13 m devices is a contact hole type.…”
mentioning
confidence: 99%
“…The expected capacitor structure for 0.13 m devices is a contact hole type. [1][2][3] This is mainly because of the difficulty in etching a noble metal electrode, such as Pt and Ru, to the node type bottom electrode with a lateral dimension of about 0.13 ϫ 0.33 m and a height larger than 0.5 m. With the hole type capacitor structure, the thin bottom electrode is deposited in the hole by a CVD technique followed by a chemical mechanical polishing ͑CMP͒ or dry etching back of the layer to separate each bottom electrode. Therefore, the difficulty in etching the bottom electrode can be eliminated.…”
mentioning
confidence: 99%
“…The oxidation resistance of both the RTN and the RTO diffusion barriers themselves was superior to that of nitride barriers ͑TiN, WN, TaN, TiAlN, TiSiN, TaSiN͒ reported by others. [7][8][9][10][11][12] In the reaction-controlled region, that is, under the thermal budgets of the capacitor fabrication processes, previously reported barriers lead to by-products on the surface of the barrier, which are either the various oxides or complexes bound with oxygen. Formed by the reaction with oxygen, the by-products such as Ti, Ta, Al, Si oxides, and various complexes, have dielectric characteristics like those of insu- lators.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, many efforts have been conducted for the use of the oxygen diffusion barrier for MIM capacitors, including binary and ternary barriers ͑TiN, TaN, WN, TiAlN, TiSiN, TaSiN͒ developed for Al and Cu metallizations. [7][8][9][10][11] However, these are not always satisfactory because of barrier oxidation. The proposed barriers for metallization do not basically prevent both the diffusion and the reaction of oxygen at high temperatures because of their high reactivity and fast diffusivity.…”
mentioning
confidence: 99%